Pengolahan Limbah Pesisir Menjadi Produk Kreatif dan Bernilai Ekonomi Berkelanjutan di Desa Sambuli - Latifa Fekri; La Ode Alirman Afu; Abdullah; Abdul Muis Balubi; Fatmawati; Asriyana; La sara; Hasan Eldin Adimu; Wa Ode Intiyani Mangurana (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
: The coastal area of Sambuli Village has considerable potential in terms of marine resources and tourism development. However, coastal waste pollution remains a persistent issue that degrades environmental quality, diminishes natural aesthetics, and reduces tourist appeal. Therefore, a training program focused on processing coastal waste into creative products can serve as an integrated solution by improving environmental cleanliness while simultaneously generating new sources of income for local communities. This community service activity aims to provide education on the importance of environmental conservation through the reduction of plastic waste, as well as to equip the community with new skills in transforming waste materials into innovative and creative handicraft products. The partners involved in this program include the Sambuli Village government and the local community of Sambuli Village, Nambo District. The methods applied in this community service program consist of community education on coastal waste management and hands-on training in recycling waste into usable products. The results indicate an increase in community awareness regarding the importance of environmental protection through waste reduction, an improvement in community skills in converting waste into creative products with economic value, and support for both the village government and the community in preserving the coastal environment while encouraging the creative use of recycled materials in Sambuli Village.